2020
DOI: 10.3390/ijms21217967
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Osteogenic Potentials of BMP-2 and FGF-2 in Extramedullary and Medullary Microenvironments

Abstract: Bone morphogenetic protein-2 (BMP-2) and fibroblast growth factor-2 (FGF-2) have been regarded as the major cytokines promoting bone formation, however, several studies have reported unexpected results with failure of bone formation or bone resorption of these growth factors. In this study, BMP-2 and FGF-2 adsorbed into atellocollagen sponges were transplanted into bone defects in the bone marrow-scarce calvaria (extramedullary environment) and bone marrow-abundant femur (medullary environment) for analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…BMPs bind to ACVR1, which locates on the cell membrane surface phosphorylating SMAD1/5/9(8). Phosphorylated SMAD1/5/9(8) combine with SMAD4 and import into the nucleus, regulating transcription that drives endochondral ossification ( Nosho et al, 2020 ). When BMP receptors bonded with Activin A, SMAD2/3 is activated to regulate inflammation ( Rautela et al, 2019 ).…”
Section: Biological Mechanisms Of Homentioning
confidence: 99%
“…BMPs bind to ACVR1, which locates on the cell membrane surface phosphorylating SMAD1/5/9(8). Phosphorylated SMAD1/5/9(8) combine with SMAD4 and import into the nucleus, regulating transcription that drives endochondral ossification ( Nosho et al, 2020 ). When BMP receptors bonded with Activin A, SMAD2/3 is activated to regulate inflammation ( Rautela et al, 2019 ).…”
Section: Biological Mechanisms Of Homentioning
confidence: 99%
“…Research shows that, the combination of BMP and FGF significantly enhanced osteogenesis than growth factor alone ( Gromolak et al, 2020 ; Hu et al, 2021 ). Bmp-2 may stimulate extramedullary bone regeneration, and FGF-2 may stimulate extramedullary bone regeneration ( Nosho et al, 2020 ). The combined use of BMP-2 and TGF-1 or TGF-3 showed stronger chondrogenic activity than BMP-2 alone ( Yu et al, 2010 ; Sang et al, 2014 ).…”
Section: Advanced Research Progress On the Biological Function Of Bmp...mentioning
confidence: 99%
“…Over 20 subgroups of BMPs are known, among which, BMP‐2 is the primary subgroup that has been used in several in vitro and in vivo studies 2 . BMP‐2 is known to strongly induce osteogenesis and it plays an important role in the development and regeneration of bone and cartilage 3 . Based on animal experiments, Li et al 4 reported an improvement in osteogenesis when BMP‐2 and BMP‐7 were sequentially released compared with that when they were released separately.…”
Section: Introductionmentioning
confidence: 99%
“…2 BMP-2 is known to strongly induce osteogenesis and it plays an important role in the development and regeneration of bone and cartilage. 3 Based on animal experiments, Li et al 4 reported an improvement in osteogenesis when BMP-2 and…”
mentioning
confidence: 99%